The Effect of Social Media Marketing and Online Travel Agents Towards The Booking Intention of Hotel in Surabaya - Ramaputra, Reza; Christiani, Natalia (Jurnal Entrepreneur dan Entrepreneurship, 2020)
Hotel occupancy rate in Surabaya experienced a declining since 2017 with the average room occupancy rate was 54% For hotel to be able to make a profit, occupancy rate must be at least 60%. As a result of this declining in occupancy, hotels in Surabaya begin to rely on e-commerce platforms as their marketing strategy to overcome this occupancy issues. Strategy that commonly used is by maximize the use of social media marketing and online travel agents. This research aims to discover whether social media marketing and Online travel agents have significant effects to the booking intention of hotel in Surabaya. This research sample uses the domestic people whoever use social media and online travel agents as a source to searching hotel information and booked a hotel room in Surabaya within a period of January 2019 to October 2019. Data research is collected by using a likert scale questionnaire that is distributed to 104 respondents. Then it proceeded by multiple linear regression similarity model with SPSS. The result shows that social media marketing has positive and significant effect towards the booking intention of hotel in Surabaya and online travel agents also has positive and significant effect towards the booking intention of hotel in Surabaya.